Analytical methodology and pharmacokinetic study of elagolix in plasma of rats using a newly developed UPLC-MS/MS assay - Qiong Wang; Er-Min Gu; Chaojie Chen; Ren-ai Xu; Shunbin Luo (Arabian Journal of Chemistry, 2021)
Elagolix, as a competitive gonadotropin-releasing hormone (GnRH) receptor antagonist, has been recently approved by the US FDA for the management of moderate to severe pain due to endometriosis in women. In this study, we developed and verified an analysis assay to detect the concentration level of elagolix in plasma from rats after sample preparation based on a newly validated ultra-performance liquid chromatography tandem mass spectrometry (UPLC-MS/MS) technique in this study. The process of sample preparation used acetonitrile for a quick and easy protein precipitation method and diazepam was engaged as the internal standard (IS). Then, gradient elution was used to elute elagolix and IS. The mobile phase used in the present experiment was consisted of solvent A (acetonitrile) and solvent B (water having formic acid with the volume ratio of 0.1%), and the type of the C18 column used was named Acquity UPLC BEH C18 column with the specification of 2.1 mm × 100 mm, 1.7 μm. Multiple reaction monitoring (MRM) in positive ion mode for the experiment was engaged to detect the level of elagolix with electrospray ionization (ESI) source by m/z 632.4 → 529.5 transition for quantification and m/z 632.4 → 177.1 transition for qualification. It was found that the method in the scope of 1–2000 ng/mL indicated excellent linearity (r2 > 0.9983). The precision of this assay for intra-day was between 3.5 and 5.5%, and for inter-day was between 9.4 and 12.7%, respectively; the accuracy was 1.2–13.9% for the intra- and inter-day. The stability, extraction recovery, and matrix effect of the method were all in accordance with the rules of assay validation in biological medium proposed by FDA, whose application was also successfully used to determine the concentration of plasma elagolix from an experiment on pharmacokinetic investigation after oral administration of 15 mg/kg elagolix.